Analysis of Demand and Supply of Sawn Timber in Lao People's Democratic Republic - Inthachack, Anousack (2000)
This study was conducted to investigate the main factors affecting supply and demand of sawn timber in Lao PDR. A market model of sawn timber consisting of supply, export and domestic demand equations, and an identity equation was formulated and developed. The partial adjustment framework for supply and demand of sawn timber was developed. Annual data for the period 1978 to 1992 were used in this study. Secondary data obtained from various sources including those published by local and international organisations and the record of relevant wood industries in Lao PDR were also used. The model was estimated using two stage least square technique (2SLS). The regression and simulation test results indicated that the estimated models were quite satisfactory. All the significant coefficients had the correct signs. The Root Mean Square Percentage Error and Their Inequality Coefficient values of the estimated models were low. The findings indicated that sawn timber price and total revenue, the latter of which was used as a proxy for total area harvested, were important factors influencing the supply of sawn timber. The supply elasticities with respect to these variables were 1.263 and 1.682, respectively. On the domestic demand side, per capita income was an important factor influencing the quantity demanded for sawn timber. The income elasticity with respect to the variable was 1.400. Two main factors that affect the quantity export demand were world per capita income and world sawn timber import price. The elasticity values with respect to these variables were -1.741 and 2.661, respectively. The findings suggest that policy variables such as annual coupe as estimated do have an impact on quantity of sawn timber supplied. This suggests that the government can influence sawn timber supply by manipulating the annual logging coupe. Demand for sawn timber, however, is more dependent on market forces, particularly by prices of sawn timber and substitute.